RETINAL VASCULAR CHANGES IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Vasilijevic, Jelena; Laban Lazovic, Marija; Pantelic, Jelica; Kalezic, Tanja; Sofronijevic, Kosana; Popovic, Andjela; Svetel, Marko; Polovina, Snezana; Kovacevic, Igor (Medical Research, 2026)
INTRODUCTION/AIM Chronic obstructive pulmonary disease (COPD) is a progressive and inflammatory disease of the airways that often leads to cardiovascular and microvascular changes. This study aimed to analyze retinal microcirculation in patients with COPD using optical coherence tomography angiography (OCTA) MATERIALS AND METHODS Cross-sectional study. A total of 44 subjects were analyzed, including 28 with COPD and 16 healthy controls. Inclusion criteria were subjects older than 18 years with a confirmed COPD diagnosis based on spirometric parameters RESULTS The statistically significant differences were observed between the groups for the following parameters: deep capillary plexus macular (p = 0.009), parafoveal (p = 0.026), and perifoveal region (p = 0.034). A significant negative correlation was observed between the ratio of residual volume to total lung capacity (RV/TLC) and the vessel density in the macular and perifoveal superficial capillary plexus regions (p<0.05). The choriocapillaris Flow also demonstrates a significant inverse relationship with the RV/TLC ratio. Regarding the deeper retinal layers, our analysis revealed a significant negative correlation between outer retina Flow and forced vital capacity (FVC). CONCLUSION Monitoring changes in the OCTA parameters, particularly in relation to lung volume parameters like RV/TLC and FVC, we conclude that OCTA may provide valuable insights into systemic vascular progression and overall severity of the disease in COPD patients